2020
DOI: 10.1111/and.13855
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the ameliorative potential of dietary supplemented selenium on doxorubicin‐induced testicular damage in mice

Abstract: Doxorubicin, a chemotherapeutic drug, is known to disrupt the normal spermatogenesis by excess oxidative stress. The present study describes the curative effects of dietary supplemented selenium on doxorubicin‐induced testicular damage in mice. Four groups were included in the study: Group I(C), Group II (Se‐0.5 ppm/kg diet), Group III (Dox‐3mg/kg body weight i.p.) and Group IV (Se + Dox). We analysed microscopic sperm parameters, histopathology, testicular germ cell kinetics, oxidative stress levels, antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…38 Moreover, maternal Se deficiencies alter the fetal development and predispose the adult offspring to thyroid dysfunction and fetal growth restriction via the alterations of mitochondrial protein expression. 39 Due to the key effect of mitochondrial dysfunctions induced by Se deficiencies on disease progression, the supplementation of antioxidant compounds including sodium selenite (Na 2 SeO 3 ), sodium selenate (Na 2 SeO 4 ) and Se enriched yeast (SY) has been applied to ameliorate the oxidative stress damage caused by the exposure of bisphenol A (BPA), 40 doxorubicin, 41 monosodium glutamate, 42 aluminum, 43 docetaxel (DTX), 44 sodium azide (SA) 45 and aflatoxin B1 (AFB1) 46 via the promotion of mitochondrial functions. Furthermore, the artificial selenylation modifications of polymannuronate, polysaccharides and galactomannan (GM) have been confirmed to promote neuroprotection, 47,48 antiinflammatory, 49,50 anti-tumor activity, 51,52 hepatic protection 53,54 and antiglycative activity 55 of these biopolymers via the promotion of antioxidant defense system.…”
Section: Discussionmentioning
confidence: 99%
“…38 Moreover, maternal Se deficiencies alter the fetal development and predispose the adult offspring to thyroid dysfunction and fetal growth restriction via the alterations of mitochondrial protein expression. 39 Due to the key effect of mitochondrial dysfunctions induced by Se deficiencies on disease progression, the supplementation of antioxidant compounds including sodium selenite (Na 2 SeO 3 ), sodium selenate (Na 2 SeO 4 ) and Se enriched yeast (SY) has been applied to ameliorate the oxidative stress damage caused by the exposure of bisphenol A (BPA), 40 doxorubicin, 41 monosodium glutamate, 42 aluminum, 43 docetaxel (DTX), 44 sodium azide (SA) 45 and aflatoxin B1 (AFB1) 46 via the promotion of mitochondrial functions. Furthermore, the artificial selenylation modifications of polymannuronate, polysaccharides and galactomannan (GM) have been confirmed to promote neuroprotection, 47,48 antiinflammatory, 49,50 anti-tumor activity, 51,52 hepatic protection 53,54 and antiglycative activity 55 of these biopolymers via the promotion of antioxidant defense system.…”
Section: Discussionmentioning
confidence: 99%
“…Dose of venlafaxine hydrochloride was selected from literature (Vollmar et al., 2009), and it is well below LD‐50. Dose of Se was chosen based on the standardisation in our laboratory as described in previously published reports (Kaur et al., 2020; Kaur et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Sperm parameters viz., Sperm concentration and sperm motility were evaluated by following the method described earlier (Kaur et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…For the study, fresh Murraya koenigii leaves were obtained from the Botanical garden of Panjab University, Chandigarh (India). Further, HEMKLE was prepared in our laboratory as described previously [13]. First of all, the leaves were rinsed with water, shade dried, and powdered.…”
Section: Preparation Of Hydroethanolic Murraya Koenigii Leaves Extrac...mentioning
confidence: 99%
“…Despite many skin-protecting properties, reports on its chemoprotective effect on skin cancer are scanty. In a previous study from our laboratory, Hydroethanolic Murraya koenigii leaves extract (HEMKLE) showed suppressive effect against chemically induced skin carcinogenesis in mice as evident through assessment of tumor statistics, oxidative stress markers, antioxidant enzymes activities, and mRNA and protein expressions of apoptosis associated markers [13]. So, by further extending our previous study, the present study was aimed (i) to assess the antiangiogenic potential of HEMKLE on chemically induced skin carcinogenesis in mice, (ii) to assess the protective effect of HEMKLE against damages incurred in liver and kidney tissues during skin carcinogenesis.…”
Section: Introductionmentioning
confidence: 97%